2007
DOI: 10.3354/dao074171
|View full text |Cite
|
Sign up to set email alerts
|

White spot syndrome virus envelope protein VP53A interacts with Penaeus monodon chitin-binding protein (PmCBP)

Abstract: White spot syndrome virus (WSSV) is the causative agent of a severe disease of cultivated shrimp. Using purified WSSV virions, VP53A encoded by open reading frame wssv067 was identified as a structural protein by SDS-PAGE and proteomics. Immunoelectron microscopy with a gold-labeled secondary antibody revealed that VP53A was distributed on the viral envelope. In order to further explore the link between WSSV067 and host proteins, we performed a yeast 2-hybrid screening of a Penaeus monodon cDNA library, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 32 publications
1
55
0
Order By: Relevance
“…1). Comparison of proPO-a and proPO-b sequences indicated that both had a microsatellite DNA site at 3 0 -UTR, but the microsatellite DNA of proPO-b contained a compound imperfect SSR, ((CT) 38 (CA) 8 (AA)(CA) 3 (TA)(CA) 14 ), which differed from the perfect SSR ((CT) 20 ) from proPO-a. The cDNA sequences of proPO-a and proPO-b prior to the microsatellite DNA site were almost identical (99% identity), but differed after the microsatellite DNA site (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…1). Comparison of proPO-a and proPO-b sequences indicated that both had a microsatellite DNA site at 3 0 -UTR, but the microsatellite DNA of proPO-b contained a compound imperfect SSR, ((CT) 38 (CA) 8 (AA)(CA) 3 (TA)(CA) 14 ), which differed from the perfect SSR ((CT) 20 ) from proPO-a. The cDNA sequences of proPO-a and proPO-b prior to the microsatellite DNA site were almost identical (99% identity), but differed after the microsatellite DNA site (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…In the previous study, authors performed a yeast-two-hybrid screening of a Penaeus monodon cDNA library, using VP53A, an envelope protein of WSSV, as bait. One of the molecules that specifically interacted with VP53A was the P. monodon chitin-binding protein (PmCBP) [13]. Although PmCBP was confirmed with the capability of binding to VP53A and chitin, its biological function remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these appear to play a critical role in anti-WSSV activity since they are associated with an ability of infected crustaceans to survive viral infection (5,17,20,30). Moreover, some proteins of shrimp, such as a chitin-binding protein and ␤-integrin, have been proposed as cellular receptors for WSSV (4,14,30). However, the mechanism by which they function as receptors is not known.…”
mentioning
confidence: 99%